2016
DOI: 10.1021/acs.langmuir.6b01867
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Stable Multifunctional Perfluorocarbon Nanoemulsions for Cancer Therapy and Imaging

Abstract: Nanotechnology provides a promising platform for drug-delivery in medicine. Nanostructured materials can be designed with desired superparamagnetic or fluorescent properties in conjunction with biochemically functionalized moieties (i.e., antibodies, peptides, and small molecules) to actively bind to target sites. These multifunctional properties make them suitable agents for multimodal imaging, diagnosis, and therapy. Perfluorohexane nanoemulsions (PFH-NEs) are novel drug-delivery vehicles and contrast agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 59 publications
1
61
0
Order By: Relevance
“…More recently, led by multidisciplinary advances in cancer nanomedicine, several nanosized PFC emulsions have been designed to accumulate in solid tumors through the enhanced permeability and retention (EPR) effect 4,20,45-47. When applied to hypoxic tumors, several recent studies have shown improved radiotherapeutic outcomes using PFC agents, even without HBO/carbogen breathing 48-50.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, led by multidisciplinary advances in cancer nanomedicine, several nanosized PFC emulsions have been designed to accumulate in solid tumors through the enhanced permeability and retention (EPR) effect 4,20,45-47. When applied to hypoxic tumors, several recent studies have shown improved radiotherapeutic outcomes using PFC agents, even without HBO/carbogen breathing 48-50.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the hydrodynamic radius and the photophysical properties of FlAsH-EDT 2 before and after labelling onto the FCM-ybbR peptide, Fluorescence Correlation Spectroscopy (FCS) was performed on a custom built confocal microscope 57 . Experiments were performed using a 488 nm blue laser (TECBL-488nm, WorldStarTech, Canada) with an excitation intensity of ~200 W/cm 2 , in order to avoid laser-induced dark states of the fluorophore.…”
Section: Methodsmentioning
confidence: 99%
“…Two-color imaging of FlAsH-FCM-ybbR immobilized on PEG-biotin-neutravidin-coated glass coverslips and labelled in situ with CoA-A647 was performed on a custom-built TIRF microscope 57 The co-localization between FlAsH and AF647 fluorescent molecules was probed using alternating excitation with a 633 nm laser for AF647 fluorescence and a 473 nm laser (Cobolt Blue, Cobolt AB, Sweden) for FlAsH fluorescence. Modulation of laser excitation was achieved using an acousto-optic tunable filter (TF625–350–2–11-BR1A, Gooch & Housego).…”
Section: Methodsmentioning
confidence: 99%
“…The nanodroplets are composed of a biocompatible phospholipid shell encapsulating an inert, non-toxic perfluorocarbon such as perfluoropentane (PFP). Hydrophobic drugs can be incorporated within the lipid shell for transport through circulation [4]. Nanoemulsions accumulate in tumors via the enhanced permeability and retention (EPR) effect, which occurs due to the inherently leaky vascular structure of tumors (Fig 1) [ [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%